Varicella meningitis in pregnancy: a clinical conundrum - Gholkar, Baljeet K.; Verghese, Lynda (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Authors present this experience of managing a case of Varicella meningitis in pregnancy in a patient presenting with headache in the third trimester. There was no history of dermatomal pain or rash. After intracranial hemorrhage and thrombosis were ruled out by imaging, a decision to perform a lumbar puncture was taken. The diagnosis was made following a PCR analysis on the cerebro-spinal fluid. Retrospective testing revealed immunity to varicella at booking, thus confirming reactivation of the infection. Treatment was done using intravenous acyclovir with complete recovery. It also created a clinical dilemma for the best possible monitoring plan for the fetus to rule out affection. A fetal medicine scan revealed no structural defects in the fetus. The subsequent pregnancy period was uneventful. A well grown normal baby was born at term. This case highlights the significance of considering a lumbar puncture in cases of intractable headache and also highlights the dilemma for fetal monitoring in such rare presentations.